Tumor Growth in the High Frequency Medulloblastoma Mouse Model Ptch1+/−/Tis21KO Has a Specific Activation Signature of the PI3K/AKT/mTOR Pathway and Is Counteracted by the PI3K Inhibitor MEN1611 - Ceccarelli, Manuela; D’Andrea, Giorgio; Micheli, Laura; Gentile, Giulia; Cavallaro, Sebastiano; Merlino, Giuseppe; Papoff, Giuliana; Tirone, Felice (Frontiers in Oncology, 2021)
We have previously generated a mouse model (Ptch1+/−/Tis21KO), which displays high frequency spontaneous medulloblastoma, a pediatric tumor of the cerebellum. Early postnatal cerebellar granule cell precursors (GCPs) of this model show, in consequence of the deletion of Tis21, a defect of the Cxcl3-dependent migration. We asked whether this migration defect, which forces GCPs to remain in the proliferative area at the cerebellar surface, would be the only inducer of their high frequency transformation. In this report we show, by further bioinformatic analysis of our microarray data of Ptch1+/−/Tis21KO GCPs, that, in addition to the migration defect, they show activation of the PI3K/AKT/mTOR pathway, as the mRNA levels of several activators of this pathway (e.g., Lars, Rraga, Dgkq, Pdgfd) are up-regulated, while some inhibitors (e.g. Smg1) are down-regulated. No such change is observed in the Ptch1+/− or Tis21KO background alone, indicating a peculiar synergy between these two genotypes. Thus we investigated, by mRNA and protein analysis, the role of PI3K/AKT/mTOR signaling in MBs and in nodules from primary Ptch1+/−/Tis21KO MB allografted in the flanks of immunosuppressed mice. Activation of the PI3K/AKT/mTOR pathway is seen in full-blown Ptch1+/−/Tis21KO MBs, relative to Ptch1+/−/Tis21WT MBs. In Ptch1+/−/Tis21KO MBs we observe that the proliferation of neoplastic GCPs increases while apoptosis decreases, in parallel with hyper-phosphorylation of the mTOR target S6, and, to a lower extent, of AKT. In nodules derived from primary Ptch1+/−/Tis21KO MBs, treatment with MEN1611, a novel PI3K inhibitor, causes a dramatic reduction of tumor growth, inhibiting proliferation and, conversely, increasing apoptosis, also of tumor CD15+ stem cells, responsible for long-term relapses. Additionally, the phosphorylation of AKT, S6 and 4EBP1 was significantly inhibited, indicating inactivation of the PI3K/AKT/mTOR pathway. Thus, PI3K/AKT/mTOR pathway activation contributes to Ptch1+/−/Tis21KO MB development and to high frequency tumorigenesis, observed when the Tis21 gene is down-regulated. MEN1611 could provide a promising therapy for MB, especially for patient with down-regulation of Btg2 (human ortholog of the murine Tis21 gene), which is frequently deregulated in Shh-type MBs.